Use of Prophylaxis for Prevention of Venous Thromboembolism in Patients with Isolated Foot or Ankle Surgery: A Systematic Review and Meta-Analysis - Bikdeli, Bavand; Visvanathan, Renuka; Jimenez, David; Monreal, Manuel; Goldhaber, Samuel Z.; Bikdeli, Behnood (Thrombosis and Haemostasis, 2019)
Although prophylaxis for venous thromboembolism (VTE) is recommended after many surgeries, evidence base for use of VTE prophylaxis after foot or ankle surgery has been elusive, leading into varying guidelines recommendations and notable practice variations. We conducted a systematic review of the literature to determine if use of VTE prophylaxis decreased the frequency of subsequent VTE, including deep vein thrombosis (DVT) or pulmonary embolism (PE), compared with control. We searched PubMed, the Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov through May 2018, for randomized controlled trials (RCTs) or prospective controlled observational studies of VTE prophylaxis in patients undergoing foot and ankle surgery. Our search retrieved 263 studies, of which 6 were finally included comprising 1,600 patients. Patients receiving VTE prophylaxis had lower risk for subsequent DVT (risk ratio [RR]: 0.72; 95% confidence interval [CI]: 0.55–0.94) and subsequent VTE (RR: 0.72; 95% CI: 0.55–0.94). There was only one case of nonfatal PE, no cases of fatal PE, and no change in all-cause mortality (RR: 3.51; 95% CI: 0.14–84.84). There was no significant difference in the risk for bleeding (RR: 2.12; 95% CI: 0.53–8.56). Very few RCTs exist regarding the efficacy and safety of VTE prophylaxis in foot and ankle surgery. Prophylaxis appears to reduce the risk of subsequent VTE, but the event rates are low and symptomatic events are rare. Future studies should determine the subgroups of patients undergoing foot or ankle surgery in whom prophylaxis may be most useful.
Keywords: venous thromboembolism; foot or ankle surgery; prophylaxis; systematic review; meta-analysis